Analisis Struktur Lapisan Fe3O4 pada Substrat Logam Tembaga dengan Metode Spin-coating: Machida Nurul Kholishoh, Darminto - Machida Nurul Kholishoh, Machida Nurul Kholishoh; Darminto, Darminto (Jurnal Fisika dan Aplikasinya, 2025)
The magnetite (Fe3O4) nanoparticle has been synthesized by coprecipitation method using iron sand as precursor of natural ferrite and polyethylene glycol(PEG)-1000 as a template. The resulted particles were then used as dispersed phase in a colloid fluid employing TMAH and water as a surfactant and carrier respectively. The fluid containing particles Fe3O4 was coated onto copper metal using a spin-coating method and followed by drying process. According to the XRD spectra and their EDX analysis, the film deposited on the Cu surface contains Fe3O4 particles with homogeneous distribution in the micrometer scale. It was observed using SEM and AFM that the particles were mainly gathered and aggregated to form clusters in the grain and the grain boundaries of Cu substrate.